2021
DOI: 10.2217/fca-2020-0213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prognosis and Outcome of Heart Failure With Reduced Ejection Fraction Patients Treated With sacubitril/valsartan According to Age

Abstract: The treatment with sacubitril/valsartan in patients suffering from chronic heart failure with reduced ejection fraction increases left ventricular ejection fraction and decreases the risk of sudden cardiac death. We conducted a retrospective analysis regarding the impact of age differences on the treatment outcome of sacubitril/valsartan in patients with chronic heart failure with reduced ejection fraction. Patients were defined as adults if ≤65 years (n = 51) and older if >65 years of age (n = 76). The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Present data obtained from this longitudinal, one-center study, demonstrated that six months treatment with Sacubitril/Valsartan had positive effects on the improvement of endothelial dysfunction and arterial stiffness in a consistent cohort HFrEF symptomatic patients, as well as a significant improvement of clinical, biochemical and haemodynamic parameters, confirming previous evidence (Armentaro et al, 2021;Pelaia et al, 2022). In accordance with a study conducted by Abumayyaleh et al (2021), conducted in patients HFrEF and stratified by age, our enrolled population is defined older (>65 years old) (mean age 69.7 ± 7.7), moreover, a further stratification of the population according to gender (82 male and 18 female) showed that there was no difference in age (male mean age 69.6 ± 7.7 and female mean age 70.4 ± 7.8, p = 0.663). Therefore, the entire population of our study can be considered older.…”
Section: Correlation Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Present data obtained from this longitudinal, one-center study, demonstrated that six months treatment with Sacubitril/Valsartan had positive effects on the improvement of endothelial dysfunction and arterial stiffness in a consistent cohort HFrEF symptomatic patients, as well as a significant improvement of clinical, biochemical and haemodynamic parameters, confirming previous evidence (Armentaro et al, 2021;Pelaia et al, 2022). In accordance with a study conducted by Abumayyaleh et al (2021), conducted in patients HFrEF and stratified by age, our enrolled population is defined older (>65 years old) (mean age 69.7 ± 7.7), moreover, a further stratification of the population according to gender (82 male and 18 female) showed that there was no difference in age (male mean age 69.6 ± 7.7 and female mean age 70.4 ± 7.8, p = 0.663). Therefore, the entire population of our study can be considered older.…”
Section: Correlation Analysissupporting
confidence: 91%
“…Data from real life showed that Sacubitril/Valsartan is associated with improvement in cardiac remodelling, New York Heart Association (NYHA) functional class and exercise tolerance with consequently hospital readmissions reduction (Armentaro et al, 2021). In addition, a study conducted by Abumayyaleh demonstrated improvement in cardiac valvular insufficiency, after 24 months of treatment with sacubitril/valsartan in patients with HFrEF (Abumayyaleh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we found significant heterogeneity among studies on some outcomes, which might result from the large differences in respect to control drugs, average dose, number of patients at different dose levels, and NYHA functional class among studies. Finally, although some studies reported that different population characteristics could have impacts on the treatment outcome with sacubitril/valsartan, such as the age and etiology differences, we did not conduct subgroup analysis ( 39 , 40 ). Because there was lack of data concerning sacubitril/valsartan therapy with respect to different ages, etiologies of HF, NYHA functional classes, control drugs, duration of follow-up, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Third, cardiac arrhythmias were not described in terms of sustained or non-sustained, fast or slow. Forth, data have shown a possible different effects of sacubitril/valsartan according to the HF etiology and age ( 42 , 43 ). Due to lack of data, the effects of sacubitril/valsartan on the risk of cardiac arrhythmias and SCD according to HF etiology and age remain unclear.…”
Section: Discussionmentioning
confidence: 99%